Natural Products for the Treatment of Type 2 Diabetes Mellitus - Ríos, José Luis (2015)
Type 2 diabetes mellitus is a metabolic disease characterized by persistent hyperglycemia. High blood sugar can produce long-term complications such as cardiovascular and renal disorders, retinopathy, and poor blood flow. Its development can be prevented or delayed in people with impaired glucose tolerance by implementing lifestyle changes or the use of therapeutic agents. Some of these drugs have been obtained from plants or have a microbial origin, such as galegine isolated from Galega officinalis, which has a great similarity to the antidiabetic drug metformin. Picnogenol, acarbose, miglitol, and voglibose are other antidiabetic products of natural origin. This review compiles the principal articles on medicinal plants used for treating diabetes and its comorbidities, as well as mechanisms of natural products as antidiabetic agents. Inhibition of α-glucosidase and α-amylase, effects on glucose uptake and glucose transporters, modification of mechanisms mediated by the peroxisome proliferator-activated receptor, inhibition of protein tyrosine phosphatase 1B activity, modification of gene expression, and activities of hormones involved in glucose homeostasis such as adiponectin, resistin, and incretin, and reduction of oxidative stress are some of the mechanisms in which natural products are involved. We also review the most relevant clinical trials performed with medicinal plants and natural products such as aloe, banaba, bitter melon, caper, cinnamon, cocoa, coffee, fenugreek, garlic, guava, gymnema, nettle, sage, soybean, green and black tea, turmeric, walnut, and yerba mate. Compounds of high interest as potential antidiabetics are: fukugetin, palmatine, berberine, honokiol, amorfrutins, trigonelline, gymnemic acids, gurmarin, and phlorizin.